PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN UNIVERSITAS TERBUKA UNIT BAHAN AJAR (PUSLABA) PONDOK CABE KOTA TANGERANG SELATAN - Al Farizsy, Razief; Suntari, Esti (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the environment and work discipline on the work performance of employees at the Open University teaching materials unit (puslaba) Pondok Cabe, South Tengerang, both partially and simultaneously. The research method used is the Quantitative method. The population in this study were employees of the Open University teaching materials unit (puslaba) totaling 69 people with a sample size of 69 respondents. The data collection technique is by means of a questionnaire. The data analysis method uses simple and multiple linear regression tests, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The research results show that: There is a positive and significant influence of the work environment on the performance of profit-making unit employees. This can be proven from the results of simple linear regression Y = 19,706 + 0.569X1. The correlation coefficient value is 0.726 (strong). The coefficient of determination value is 52.7%, and the tcount value is 8.632 > ttable 1.996 with a significance of 0.000 < 0.05. There is a positive and significant influence of work discipline on the performance of profit-making unit employees. This can be proven from the results of simple linear regression Y = 8,000 + 0.789X2. The correlation coefficient value is 0.930 (very strong). The coefficient of determination value is 86.5%, and the tcount value is 12.427 > ttable 1.996 with a significance of 0.000 < 0.05. Simultaneously there is a positive and significant influence between the work environment and work discipline on the performance of profit-making unit employees. This can be proven from the results of multiple linear regression Y = 5,624 + 0.177X1 + 0.688X2. The coefficient of determination value is 52.7%, and the fcount value is 85.303 > ftable 2.74 with a significance of 0.000 < 0.05.